KAJIAN LITERATUR TENTANG PENGARUH MINDFULNESS TERHADAP PENGURANGAN STRES AKADEMIK PADA MAHASISWA - Prima Intan Ratna Sari; Risma Ayu Sulityowati, Noer Aini Eldi, Muhammad Ilham Wakita, Setianingrum Prima Intan (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
This study aims to compile a literature review on the effect of mindfulness on reducing academic stress in college students. This study analyzes findings from various relevant studies to identify the mechanisms of mindfulness's effectiveness in reducing stress, as well as providing practical recommendations for higher education institutions. The research findings indicate that mindfulness is effective in reducing stress levels, improving psychological well-being, and supporting academic adaptation. In addition, mindfulness-based applications have proven to be an easily accessible solution for students to practice mindfulness independently. However, challenges such as sustainability of practice and cultural adaptation require further attention. By integrating mindfulness into the curriculum and student services, higher education institutions can create a more supportive and conducive learning environment for students' mental health. This study presents strategic recommendations for educators, practitioners, and policymakers to improve the effectiveness of mindfulness programs in academic settings